Asymmetrism and the magnitudes of welfare benefits - Forcehimes, Andrew T. (2020)
One vexing question for Desire Satisfactionism is this: At what time do you benefit from a satisfied desire? Recently Eden Lin has proposed an intriguing answer. On this proposal – Asymmetrism – when past-directed desires are satisfied, the time interval during which you benefit is the time of the desire; and, when future-directed desires are satisfied, the time interval during which you benefit is the time of the object. In this essay, I argue that Asymmetrism forces us to give implausible answers to a different question: To what extent does a given satisfied desire benefit you?